Maternal Genetic Risk for Depression and Child Human Capital - Giorgia Menta; Anthony Lepinteur; Andrew E. Clark; Simone Ghislandi; Conchita D'Ambrosio (Institute of Labor Economics (IZA), 2022)
We here address the causal relationship between the maternal genetic risk for depression and child human capital using UK birth-cohort data. We find that an increase of one standard deviation (SD) in the maternal polygenic risk score for depression reduces their children's cognitive and non-cognitive skill scores by 5 to 7% of a SD throughout adolescence. Our results are robust to a battery of sensitivity tests addressing, among others, concerns about pleiotropy and dynastic effects. Our Gelbach decomposition analysis suggests that the strongest mediator is genetic nurture (through maternal depression itself), with genetic inheritance playing only a marginal role.
Keywords: I14; J24; 330; maternal depression; human capital; ALSPAC